Research Agendas in an Ubuntu Paradigm - Maren Seehawer (University of Johannesburg, 2023)
The article contributes to the ongoing scholarly exploration of Ubuntu as an indigenous Southern African research paradigm. Building on an understanding of Ubuntu as humanness that embraces the interconnectedness not only of humans, but of all creation, the article emphasises that how we research is inseparable from what is researched. Being human in the sense of Ubuntu is not passive but depends on our continued enacting of our humanness through relating positively to others. On this basis, being/becoming human is understood as an inherent (research) agenda in the Ubuntu paradigm. It is proposed that Ubuntu accommodates research agendas that recognise the interdependence of humans with other humans, other species and our shared planet and that aim at balancing these relationships in search of humble togetherness. Ubuntu research agendas seek to contribute to the healing of our planet's human made colonial and ecological conditions locally or globally.